Effects of reclaimed asphalt pavement on indirect tensile strength test of foamed asphalt mix tested in dry condition - Katman H.Y.; Ibrahim M.R.; Matori M.Y.; Norhisham S.; Ismail N. (Institute of Physics Publishing, 2023)
Indirect tensile strength (ITS) test was conducted to analyse strength of the foamed asphalt mixes incorporating reclaimed asphalt pavement. Samples were tested for ITS after cured in the oven at 40C for 72 hours. This testing condition known as dry condition or unconditioned. Laboratory results show that reclaimed asphalt pavement (RAP) contents insignificantly affect the ITS results. ITS results significantly affected by foamed bitumen contents. Published under licence by IOP Publishing Ltd.